2022
DOI: 10.3390/jcdd9060185
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetics and Congenital Heart Diseases

Abstract: Congenital heart disease (CHD) is a frequent occurrence, with a prevalence rate of almost 1% in the general population. However, the pathophysiology of the anomalous heart development is still unclear in most patients screened. A definitive genetic origin, be it single-point mutation or larger chromosomal disruptions, only explains about 35% of identified cases. The precisely choreographed embryology of the heart relies on timed activation of developmental molecular cascades, spatially and temporally regulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 114 publications
0
3
0
Order By: Relevance
“…It has been shown that congenital heart defects noted in CPs may encompass a wide spectrum of abnormalities such as (1) tetralogy of Fallot (Coffin-Siris syndrome, CHARGE syndrome, Sifrim-Hitz-Weiss syndrome, Kleefstra syndrome, and Cornelia de Lange syndrome), (2) atrial septal defect (Coffin-Siris syndrome, Sifirim-Hitz-Weiss syndrome, Kabuki syndrome, Kleefstra syndrome, Wolf-Hirschorn syndrome, Rubinstein-Taybi syndrome, Microphthalmia syndromic 2, Cornelia de Lange syndrome, Intellectual disability-hypotonic facies syndrome X-linked, and Immunodeficiency-centromeric instability-facial anomalies syndrome 1), (3) ventricular septal defect (Coffin-Siris syndrome, CHARGE syndrome, Sifrim-Hitz-Weiss syndrome, Kabuki syndrome, Kleefstra syndrome, Rubinstein-Taybi syndrome, Microphthalmia syndromic 2, Cornelia de Lange syndrome, and Immunodeficiency-centromeric instability-facial anomalies syndrome 1), (4) interrupted aortic arch (CHARGE syndrome), (5) pulmonary stenosis (CHARGE syndrome, Kleefstra syndrome, Cornelia de Lange syndrome, and Intellectual disability-hypotonic facies syndrome X-linked), (6) aortic stenosis (Intellectual disability-hypotonic facies syndrome X-linked), (7) patent ductus arteriosus (Coffin-Siris syndrome, CHARGE syndrome, Sifrim-Hitz-Weiss syndrome, Cornelia de Lange syndrome, and Intellectual disability-hypotonic facies syndrome X-linked), (8) mitral valve anomalies (Microphthalmia syndromic 2), and (9) double-outlet right ventricle (CHARGE syndrome) (Linglart and Bonnet 2022 ).…”
Section: Clinical Manifestation and Common Phenotypic Featuresmentioning
confidence: 99%
“…It has been shown that congenital heart defects noted in CPs may encompass a wide spectrum of abnormalities such as (1) tetralogy of Fallot (Coffin-Siris syndrome, CHARGE syndrome, Sifrim-Hitz-Weiss syndrome, Kleefstra syndrome, and Cornelia de Lange syndrome), (2) atrial septal defect (Coffin-Siris syndrome, Sifirim-Hitz-Weiss syndrome, Kabuki syndrome, Kleefstra syndrome, Wolf-Hirschorn syndrome, Rubinstein-Taybi syndrome, Microphthalmia syndromic 2, Cornelia de Lange syndrome, Intellectual disability-hypotonic facies syndrome X-linked, and Immunodeficiency-centromeric instability-facial anomalies syndrome 1), (3) ventricular septal defect (Coffin-Siris syndrome, CHARGE syndrome, Sifrim-Hitz-Weiss syndrome, Kabuki syndrome, Kleefstra syndrome, Rubinstein-Taybi syndrome, Microphthalmia syndromic 2, Cornelia de Lange syndrome, and Immunodeficiency-centromeric instability-facial anomalies syndrome 1), (4) interrupted aortic arch (CHARGE syndrome), (5) pulmonary stenosis (CHARGE syndrome, Kleefstra syndrome, Cornelia de Lange syndrome, and Intellectual disability-hypotonic facies syndrome X-linked), (6) aortic stenosis (Intellectual disability-hypotonic facies syndrome X-linked), (7) patent ductus arteriosus (Coffin-Siris syndrome, CHARGE syndrome, Sifrim-Hitz-Weiss syndrome, Cornelia de Lange syndrome, and Intellectual disability-hypotonic facies syndrome X-linked), (8) mitral valve anomalies (Microphthalmia syndromic 2), and (9) double-outlet right ventricle (CHARGE syndrome) (Linglart and Bonnet 2022 ).…”
Section: Clinical Manifestation and Common Phenotypic Featuresmentioning
confidence: 99%
“…Congenital heart disease (CHD) is currently the most common type of birth defect in the general population with an incidence of about 1% ( Linglart and Bonnet, 2022 ). Interestingly, few studies have identified the role of RNA editing in CHD.…”
Section: Adar1 In Cvdsmentioning
confidence: 99%
“…These encompass chromosomal aneuploidy such as Down syndrome and Turner syndrome, copy number variants such as 22q11 deletion syndrome and Williams-Beuren syndrome, single gene mutation syndromes like Alagille, Noonan, or CHARGE syndromes [20][21][22][23][24], and several monogenic non-syndromic lesions. Genetic entities are characterized by incomplete penetration and variable expression [23,25]. In addition to genetics, maternal obesity, diabetes, tobacco exposure, alcohol intake, teratogenic medications, and infections such as rubella are known causes [23,25].…”
Section: Introductionmentioning
confidence: 99%
“…Genetic entities are characterized by incomplete penetration and variable expression [23,25]. In addition to genetics, maternal obesity, diabetes, tobacco exposure, alcohol intake, teratogenic medications, and infections such as rubella are known causes [23,25]. The majority of disease presentations are non-syndromic with no distinct cause [18,21].…”
Section: Introductionmentioning
confidence: 99%